Disruptive behavior in the operating room: prevalence, consequences, prevention, and management. Issue 3 (June 2018) - Villafranca, Alexander; Fast, Ian; Jacobsohn, Eric
Abstract : Purpose of review: Disruptive workplace behavior can have serious consequences to clinicians, institutions, and patients. There is a range of disruptive behaviors, and the consequences are often underappreciated. The purpose of this manuscript is to review the definition, prevalence, consequences, prevention, and management of disruptive behavior in the operating room. Recent findings: Although a small minority of operating room clinicians act disruptively, 98% of clinicians report having recently been exposed to disruptive behavior, with the average being 64 events per clinician per year. The causes include intrapersonal factors, workplace relationships, workplace logistics, and broader contextual factors. Disruptive behavior undermines patient care by decreasing individual and team clinical performance. It decreases clinician well being, sets a poor example for medical students who are susceptible to negative role models, and decreases hospital efficiency. The way that clinicians respond to disruptive behavior may either exacerbate or reduce the consequences of the behavior. In order to prevent disruptive behavior, the causes must be addressed. Institutions must have robust policies to deal with disruptive behavior and have preventive measures that include regular staff education. Whenever disruptive behavior does occur, it must be expeditiously addressed, which may include graded discipline. Summary: Disruptive intraoperative behavior is prevalent and harms multiple parties in the operating room. Institutions require comprehensive measures to prevent the behavior and to mitigate consequences.